Catalog of type specimens of invertebrates in the collection of the Instituto Nacional de Pesquisas da Amazônia, Manaus, Brazil. VI. Hexapoda: Hemiptera: Heteroptera - Rodrigues, Higor D.d.; Ferreira-Keppler, Ruth L. (Zootaxa, 2013)
A catalog of type specimens of Heteroptera (Insecta: Hemiptera) deposited in the Instituto Nacional de Pesquisas da Amazônia (INPA), Manaus, Brazil, is presented and updated to May, 2012. A total of 37 holotypes and 61 lots of paratypes of 78 species are listed in their families: Miridae and Reduviidae (infraorder: Cimicomorpha); Mesoveliidae and Veliidae (Gerromorpha); Belostomatidae, Naucoridae, and Notonectidae (Nepomorpha); and Coreidae, Geocoridae [the older sense of “Lygaeidae”], and Pentatomidae (Pentatomomorpha). The taxa are presented alphabetically by infraorders, families, and genera, followed by epithet, bibliographic citation, type category, collection number, method of preservation, and present data on the labels. When necessary, we added localities data, and changes in taxonomic status of some species.